2013
DOI: 10.1111/bjh.12335
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies and monoclonal gammopathy in Gaucher disease; a systematic review of the literature

Abstract: SummaryGaucher disease is an autosomal, recessively inherited, lysosomal storage disease, which has been associated with gammopathies and malignancies. This report represents the results of a systematic review of the literature on the prevalence of monoclonal gammopathies and malignancies in Gaucher disease. A PubMed search identified 365 studies, of which 80 reported on concomitant Gaucher disease and malignancies and/or gammopathies (15 cohort/cross sectional studies, and 65 case reports/series). Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 103 publications
4
100
0
9
Order By: Relevance
“…41 However, in a recent review of literature 42 which included 15 cohort/cross sectional studies, and 65 case reports/series, it was concluded that GD patients have an increased risk of cancer in general [pooled relative risk of 1$70 (95% confidence interval 1$27-2$31)] and multiple myeloma and hematological malignancies in particular (estimated risk between 25$0 and 51$1 and 3$5 and 12$7, respectively). An increased risk of hepatocellular carcinoma and renal cell carcinoma has also been reported.…”
Section: Malignancies In Gaucher Diseasementioning
confidence: 99%
“…41 However, in a recent review of literature 42 which included 15 cohort/cross sectional studies, and 65 case reports/series, it was concluded that GD patients have an increased risk of cancer in general [pooled relative risk of 1$70 (95% confidence interval 1$27-2$31)] and multiple myeloma and hematological malignancies in particular (estimated risk between 25$0 and 51$1 and 3$5 and 12$7, respectively). An increased risk of hepatocellular carcinoma and renal cell carcinoma has also been reported.…”
Section: Malignancies In Gaucher Diseasementioning
confidence: 99%
“…Clinical and experimental studies have shown that GD patients exhibit various immunological abnormalities, such as increased susceptibility to infections (Aker et al 1993;Maródi et al 1995), numerical dendritic cell defects (Micheva et al 2006), and an increased incidence of B-lymphoproliferative disorders and solid tumors (Arends et al 2013). Laboratory findings include elevated levels of acute-phase proteins (Rogowski et al 2005) and serum immunoglobulin levels (de Fost et al 2008), frequent occurrence of monoclonal gammopathy (Arends et al 2013), detection of various autoantibodies in patients' serum (Shoenfeld et al 1995), and increased plasma levels of proinflammatory cytokines, including IL-1b, IL-6, IL-8, IL-10, TNF-a, and TGF-b (Allen et al 1997;Barak et al 1999;Michelakakis et al 1996;Deegan et al 2005;Pérez Calvo et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory findings include elevated levels of acute-phase proteins (Rogowski et al 2005) and serum immunoglobulin levels (de Fost et al 2008), frequent occurrence of monoclonal gammopathy (Arends et al 2013), detection of various autoantibodies in patients' serum (Shoenfeld et al 1995), and increased plasma levels of proinflammatory cytokines, including IL-1b, IL-6, IL-8, IL-10, TNF-a, and TGF-b (Allen et al 1997;Barak et al 1999;Michelakakis et al 1996;Deegan et al 2005;Pérez Calvo et al 2000). These findings imply that chronic inflammatory status possibly reflects a chronic stimulation of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…44 Other possible factors implicated in the pathophysiology of cancer in Gaucher disease include splenectomy, endoplasmic reticulum stress, genetic modifiers, altered iron metabolism and insulin resistance. 45 A single-centre cohort study of 131 patients with Gaucher disease of mixed ancestry in Western Europe investigated cancer incidence and mortality compared with controls. 46 A 2.5-fold (95 % confidence interval [CI] 1.1-4.7) increased incidence of cancer was reported and a 12.7-fold (95 % CI 2.6-37.0) increased risk of haematological cancers.…”
Section: Gaucher Disease and Haematological Malignanciesmentioning
confidence: 99%
“…Immune and haematological malignancies [3.5-12.7]). 45 An association between Gaucher disease and myelodysplastic syndrome has been reported but is rare. 51 Epidural haematoma in Gaucher disease is a rare manifestation that mimics malignant processes.…”
Section: Gaucher Disease and Haematological Malignanciesmentioning
confidence: 99%